Depression and quality of life in patients with epilepsy in Northwest Greece. (March 2019) - Siarava, Eleftheria; Hyphantis, Thomas; Katsanos, Aristeidis H.; Pelidou, Sygkliti-Henrietta; Kyritsis, Athanassios P.; Markoula, Sofia
Highlights: Patients with epilepsy have more frequent and severe depression compared to healthy controls in Northwest Greece. Patients with epilepsy have a poorer quality of life compared to healthy controls in Northwest Greece. The adverse effects of Antiepileptic drugs (AEDs) are associated to the incidence of depression and its severity. The adverse effects of AEDs and depression are the most significant of the examined parameters in quality of life. Abstract: Purpose: The purpose of the present study was to compare depression and QoL between patients with epilepsy and healthy controls, evaluating potentially related factors to depression and QoL in patients with epilepsy in Northwest Greece. Methods: A case study was conducted in adult patients with epilepsy followed up at the University Hospital of Ioannina and in healthy controls. The Patient Health Questionnaire (PHQ-9) for depression's severity evaluation, the WHOQOL-BREF questionnaire for the QoL estimation and the Adverse Event Profile (AEP) questionnaire for the Antiepileptic Drugs (AEDs) adverse effects assessment were used. Results: Seventy patients with epilepsy and 70 controls were recruited. The PHQ-9 score was higher in patients compared to controls and slightly higher than reported in patients with epilepsy. PHQ-9 was significantly associated with the AEP score. Our patients had a poorer QoL compared to controls. The level of education, the AEP and the PHQ-9 scores were associated to QoL, the last two being the most powerful predictors of QoL. Conclusion: Patients with epilepsy in Northwest Greece had higher rates of depression than reported in patients with epilepsy and poorer QoL compared to controls. The adverse effects of AEDs were related to depression in our study, while the adverse effects of AEDs and depression were more powerful predictors of QoL compared to demographics and other characteristics of epilepsy.